Iteron inhibition of plasmid RK2 replication in vitro: evidence for intermolecular coupling of replication origins as a mechanism for RK2 replication control. - Kittell, B L (1991)
The broad-host-range plasmid RK2 and its derivatives are maintained in Gram-negative bacteria at a specific copy number that appears to be determined by a series of direct repeats (iterons) located at the RK2 replication origin and by the RK2 replication initiation protein. TrfA. An in vitro replication system was developed from Escherichia coli that is active with either the intact eight-iteron RK2 origin or a minimal five-iteron RK2 origin when purified TrfA protein is provided. Using this in vitro replication system, we have examined the mechanism(s) of copy-number control. It was found that two or more RK2 iterons present on a supercoiled compatible plasmid molecule are capable of specifically inhibiting in vitro the replication of either functional RK2 origin plasmid and that this inhibition is not overcome by adding increasing amounts of TrfA protein. A mutant TrfA protein, TrfA-33(cop254D), that increases the copy number of an RK2 origin in vivo exhibits replication kinetics and activity levels in this in vitro system similar to that of the wild-type protein. However, RK2 in vitro replication initiated by TrfA-33(cop254D) has a much reduced sensitivity to iteron inhibition. These data support a model for RK2 copy-number control that involves intermolecular coupling between TrfA-bound iterons.